Relative DNA content in diploid, polyploid, and multiploid species of Paspalum (Poaceae) with relation to reproductive mode and taxonomy - Galdeano, Florencia (2016)
Fil: Galdeano, Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias. Instituto de Botánica del Nordeste; Argentina.